2023
DOI: 10.3390/jcm12124150
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Probiotics, Prebiotics, and Synbiotics in Patients Who Have Undergone Abdominal Operation, in Terms of Bowel Function Post-Operatively: A Network Meta-Analysis

Abstract: Background: Abdominal operations may lead to post-operative bowel dysfunction, while administration of probiotics, prebiotics and synbiotics may limit its manifestation. Τhe study aimed to assess the efficacy of probiotics, prebiotics and synbiotics in patients who undergone abdominal operation, in terms of bowel function post-operatively. Methods: PubMed, Scopus, Cochrane Central Register of Controlled Trials (Central), Embase, US Registry of clinical trials, and sources of grey literature were searched. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Recent research reports probiotics can be used as supplements in the prevention and treatment of infectious diseases [ 42 ]. A network meta-analysis conducted by Ioannidis et al reported the efficacy of probiotics, prebiotics and synbiotics in patients who have undergone an abdominal operation, in terms of bowel function post-operatively [ 43 ].…”
Section: Probiotics As Natural Therapeutic Agentsmentioning
confidence: 99%
“…Recent research reports probiotics can be used as supplements in the prevention and treatment of infectious diseases [ 42 ]. A network meta-analysis conducted by Ioannidis et al reported the efficacy of probiotics, prebiotics and synbiotics in patients who have undergone an abdominal operation, in terms of bowel function post-operatively [ 43 ].…”
Section: Probiotics As Natural Therapeutic Agentsmentioning
confidence: 99%
“…Today, many in vitro and in vivo studies have shown that probiotics exert potential suppressive effects on various infectious and inflammatory conditions, thus significantly shortening the inflammatory phase of the wound healing process [115][116][117]. At the same time, there are quite a lot of clinical studies referring to the reduction in postoperative bloating and the shortening of the time duration up to the first flatus, all indirectly indicating the shortening of the postoperative paralytic ileus [118][119][120]. Both the above [115][116][117][118][119][120] may not have a direct, suppressive effect on the pain originating from abdominal wall trauma, or from the distension of the gut wall, but there are many studies documenting the specific cytokine and other molecular changes which point in that direction.…”
Section: Probiotics In Postoperative Pain Managementmentioning
confidence: 99%